2017
DOI: 10.1139/as-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Syngenetic dynamic of permafrost of a polar desert solifluction lobe, Ward Hunt Island, Nunavut

Abstract: Repeated freeze-thaw cycles on slopes trigger sorting and solifluction mass movements, while subsequent displacement of material modifies the geomorphology of slopes as well as permafrost dynamics. This study focuses on the geomorphology and the cryostratigraphy of a polar desert stone-banked solifluction lobe with the objective to clarify the impact of slow mass movements on ground ice aggradation. The morphology of the solifluction lobe was characterized by peripheral ridges of coarse gravel, partially surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…This deposition process could explain the absence of sorting in Sp-4 as well as the increasing amounts of fines and the decreasing amount of carbonates Bulk density (g cm towards the soil surface. Similar stratigraphic evidence was found where surface runoff and seepage occurs (Woo and Steer 1986;Woo and Xia 1995) and has also been reported at another site on Ward Hunt Island (Verpaelst et al 2017).…”
Section: Discussionsupporting
confidence: 86%
“…This deposition process could explain the absence of sorting in Sp-4 as well as the increasing amounts of fines and the decreasing amount of carbonates Bulk density (g cm towards the soil surface. Similar stratigraphic evidence was found where surface runoff and seepage occurs (Woo and Steer 1986;Woo and Xia 1995) and has also been reported at another site on Ward Hunt Island (Verpaelst et al 2017).…”
Section: Discussionsupporting
confidence: 86%
“…From there, however, the subsurface flow can take two pathways. It can follow a path where the deposition of fine sediment has created suitable conditions for the formation of solifluction lobes, which diffuses the water through its ridges into a colluviums slope 20 . It can also evolve into a blockstream, which maintains rapid flow because of its large pore sizes.…”
Section: Discussionmentioning
confidence: 99%
“…17 This occurs as the water is funneled into the path of least resistance through coarse areas of slopes and patterned ground, traveling in similar fashion to vertical funnel flow. 18 It has been suggested that patterned ground in such regions may be created by a mix of periglacial sorting processes, leaching, and lessivage, 19,20 with the capacity to increase the hydraulic conductivity of the substrate by at least an order of magnitude. 21 Underground erosion in patterned ground has already been reported in the literature, as a process enhancing the surface expression of sorted stripes on frost-affected slopes.…”
Section: Introductionmentioning
confidence: 99%
“…Their importance in the periglacial landscape extends beyond that of a simple hydrological pathway, as they play specific roles in heat transfer and active layer development (Gooseff et al, ; Hastings, Luchessa, Oechel, & Tenhunen, ; Levy & Schmidt, ; Paquette, Fortier, Mueller, Sarrazin, & Vincent, ; Paquette, Fortier, & Vincent, ), solute transport (Levy, Fountain, Gooseff, Welch, & Lyons, ), and nutrient and carbon cycling (Ball & Levy, ; Cheng et al, ; Mcnamara, Kane, Hobbie, & Kling, ; Oberbauer, Tenhunen, & Reynolds, ). They also play a role in the development of the landscape, acting as an immature drainage network (Mcnamara, Kane, & Hinzman, ), as moisture provider for slow mass wasting processes (Verpaelst, Fortier, Kanevskiy, Paquette, & Shur, ), or as indications of denudation by leaching of fine material (Paquette et al, ).…”
Section: Introductionmentioning
confidence: 99%